Factor Supplies and the Direction of Technical Change - Helena Svaleryd; Jonas Vlachos (The Research Institute of Industrial Economics (IUI), 2005)
In this paper, we empirically address the hypothesis that there is a relationship between the supply of human capital and the rate and direction of skill-biased technical change (SBTC). Using country- and industry-level data on OECD countries, we find R&D to be positively related to the supply of human capital. There is, however, no indication that this translates into higher rates of SBTC, when SBTC is measured as changes in the wage bill share of skilled labor. Interestingly, both R&D and the rate of SBTC seem to be relatively high in low-skill industries in countries where the supply of human capital is relatively high.
Keywords: J32; O31; 330; Skilled-biased Technical Change; Supply of Human Capital; Humankapital; Technischer Fortschritt; Industrielle Forschung; OECD-Staaten